AB0364 Relationship between Self Esteem and Rheumatoid Arthritis. (10th June 2014) - Lakhdar, T.; Allali, F.; Ben Slama, I.; El Kabbaj, S.; Medrare, L.; Ngeuleu, A.; Rkain, H.; Hajjaj-Hassouni, N.
Abstract : Background: Research on patients with chronic illness has demonstrated that self-esteem is related to the reported level of physical restrictions, functional status and perceiption of symptom severity. Previous literature suggests that low self-esteem causes more negative affect for chronic disease patients than healthy populations. Objectives: This study aims to evaluate the frequency of low self esteem in patients with rheumatoid arthritis (RA) and to identify factors influencing it. Methods: It is a cross-sectional study including 103 patients with RA. The demographic characteristics of patients and the characteristics of RA were collected. Pain and fatigue were assessed using the analogic visual scale (0-100 mm), the disease's activity was evaluated by DAS-28 ESR, the functionnal disability by the arabic version of the health assessment questionnaire (HAQ), and the the psychological state by the arabic version of the questionnaire Hospital Anxiety and Depression (HAD). The level of self-esteem was measured using the Rosenberg Self-esteem Scale (RSES). Participants have reported their agreement, on a five-point Likert scale (0 = strongly disagree, 4 = strongly agree) on 10 statements concerning self-perceived aspects of self-esteem. Total scores range from 10-40. A low self esteem rate was defined by a general scroe less than 31 1 . Results: 103 patients were included with a mean age of 49.7±11.4 years and a female predominance (90 (87.4%)). The median of RA duration was 8.16 years [3.25 to 14.16]. The average DAS28 - ESR was 4.28±1.75, with a median HAQ 0.5 [0 -1.37]. 58 patients (56.3%) have low self esteem. Low self-esteem was significantly associated to a high activity of the RA (OR=1.652, IC95% [1.254-2.176], p<0.001), to an important functional disability (OR=3.114, IC95% [1.676-5.786], p<0.001), greater pain severity VAS (OR=1.021; IC95% [1, 006-1, 035]; p=0, 005), increased fatigue VAS (OR=1, 020; IC95% [1, 005-1, 035]; p=0, 009), to anxiety (OR=1.189, IC95% [1.073-1.317], p<0.001) and to depression (OR=1.298, IC95% [1.161-1.499], p<0.001). After a multivariate analysis, depression was the only determinant significantly associated to a low self esteem. Conclusions: This study suggests that low self esteem is frequent in patients suffering from RA, wich may be linked to depressive tendency. Therefore, patients with chronic disease, who already face additional medical and psychosocial burden, may benefit from interventions designed to bolster self-esteem in the ongoing context of self-care. References: Traduction et validation canadienne-française de l'échelle de l'estime de soi de Rosenberg; Έvelyne F. Vallières et Robert J. Vallerand, 1990: International Journal of Psychology 25, 305-316. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4807